The Association Between Perceived Stress and Quality of Life in University Students: The Parallel Mediating Role of Depressive Symptoms and Health-Promoting Behaviors - Seo, Eun Ji; Ahn, Jeong-Ah; Hayman, Laura L.; Kim, Chun-Ja (Asian nursing research, 2018)
This study examined whether depressive symptoms and health-promoting lifestyle behaviors mediate the association between perceived stress and quality of life (QoL) in university students. Using a cross-sectional survey, Korean university students (N = 187, M = 23.97 years; 54.0% Woman) completed structured questionnaires with psychometric adequacy. A parallel multiple mediation model was used to test the mediating effect of depressive symptoms and health-promoting lifestyle behaviors on the relationship between perceived stress and QoL. Total effect of perceived stress, depressive symptoms, and health-promoting lifestyle behaviors on QoL was -.55. Of these, total indirect mediating effect was -.50, whereas direct effect was only -.05 in the parallel mediation model. In particular, depressive symptoms (indirect effect = -.32) and health-promoting lifestyle behaviors (indirect effect = -.18) completely mediated the relationship between perceived stress and QoL. The results suggest that effective strategies primarily focusing on improving depressive symptoms along with health behaviors are needed to decrease the negative effect of perceived stress on QoL.